Single-Cell Transcriptomics Uncovers Cellular Heterogeneity, Mechanisms, and Therapeutic Targets for Parkinson’s Disease - Huang, Jianjun; Liu, Li; Qin, Lingling; Huang, Hehua; Li, Xue (Frontiers in Genetics, 2022)
Objective: This study aimed to exploit cellular heterogeneity for revealing mechanisms and identifying therapeutic targets for Parkinson’s disease (PD) via single-cell transcriptomics. Methods: Single-cell RNA sequencing (scRNA-seq) data on midbrain specimens from PD and healthy individuals were obtained from the GSE157783 dataset. After quality control and preprocessing, the principal component analysis (PCA) was presented. Cells were clustered with the Seurat package. Cell clusters were labeled by matching marker genes and annotations of the brain in the CellMarker database. The ligand–receptor networks were established, and the core cell cluster was selected. Biological functions of differentially expressed genes in core cell clusters were analyzed. Upregulated marker genes were identified between PD and healthy individuals, which were measured in 18 PD patients’ and 18 healthy individuals’ blood specimens through RT-qPCR and Western blotting. Results: The first nine PCs were determined, which can better represent the overall change. Five cell clusters were identified, including oligodendrocytes, astrocytes, neurons, microglial cells, and endothelial cells. Among them, endothelial cells were the core cell cluster in the ligand–receptor network. Marker genes of endothelial cells possessed various biological functions. Among them, five marker genes (ANGPT2, APOD, HSP90AA1, HSPA1A, and PDE1C) were upregulated in PD patients’ than in healthy individuals’ endothelial cells, which were confirmed in PD patients’ than in healthy individuals’ blood specimens. Conclusion: Our findings revealed that the cellular heterogeneity of PD and endothelial cells could play a major role in cell-to-cell communications. Five upregulated marker genes of endothelial cells could be underlying therapeutic targets of PD, which deserve more in-depth clinical research.